Near-infrared reflectance spectroscopy calibrations for sorghum silage - P.C. Dubois; G. Garcia; K.K. Bolsen; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1989)
Calibrations for near-infrared reflectance spectroscopy (NIRS) analysis of sorghum silage and sheep feces samples were developed. with mixed success. For sorghum silage, the standard errors of calibration (SEC) and correlation coefficients of calibration (R2) for crude protein (CP) were .405% and .927; for acid detergent fiber (ADF), 1.667% and .943; and for neutral detergent fiber (NDF), 1.589% and .964, respectively. The statistics for crude protein were not as good as similar work reported in the literature, but the data for the fiber components was as good as or better than similar reported work. For sheep feces. the SEC and R2 for CP were .300% and .949; for ADF. 1.438% and .875; and for NDF. 2.016% and .846, respectively. These statistics are similar to other reports. Calibration should improve as we add more calibration samples.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Spectroscopy; Sorghum silage